Analisis Faktor-faktor yang Mempengaruhi Jumlah Kelahiran di Jorong Ngungun Menggunakan Analisis Diskriminan - Rahmi Biuty Riva Hani; Helma Helma (UNIVERSITAS NEGERI PADANG, 2021)
Birth is one of the factors causing the increase in population. The high number of births will lead to uncontrolled economic growth of the country so that many people experience poverty. The purpose of this study was to determine the shape of the discriminant equation and the factors that most influence the number of births in Jorong Ngungun by using discriminant analysis. The data analysis carried out is to determine the correlation between variables, perform principal component analysis, perform cluster analysis, form discriminant analysis equations, test the significance of the discriminant function, test the independent variables that distinguish groups, test the validity of discriminant analysis, and interpret the results of the analysis. Based on the research, the independent variables that most influence the number of births in Jorong Ngungun are the number of family members in one family card and the amount of income in one month.